2018
DOI: 10.1136/injuryprev-2017-042676
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of an opioid overdose prevention intervention delivered subsequent to acute care

Abstract: NCT0178830; Results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 34 publications
(18 reference statements)
0
57
0
Order By: Relevance
“…Trainings by first responders or in ED could be particularly effective given that a history of overdose is a strong predictor of subsequent overdose, though research suggests that witnessing an overdose is a stronger predictor of naloxone uptake than personal experience of overdose [23,[29][30][31]. Prior research has also demonstrated that patients generally accept take-home naloxone kits when offered in the ED [29], however there is some evidence to show that overdose prevention interventions among those at risk in the ED may not have an impact on subsequent overdose [32]. Efforts to promote initiation of opioid agonist treatment in the ED may be an efficient and effective strategy to reduce overdose mortality [33].…”
Section: Discussionmentioning
confidence: 99%
“…Trainings by first responders or in ED could be particularly effective given that a history of overdose is a strong predictor of subsequent overdose, though research suggests that witnessing an overdose is a stronger predictor of naloxone uptake than personal experience of overdose [23,[29][30][31]. Prior research has also demonstrated that patients generally accept take-home naloxone kits when offered in the ED [29], however there is some evidence to show that overdose prevention interventions among those at risk in the ED may not have an impact on subsequent overdose [32]. Efforts to promote initiation of opioid agonist treatment in the ED may be an efficient and effective strategy to reduce overdose mortality [33].…”
Section: Discussionmentioning
confidence: 99%
“…For harm reduction interventions to be efficacious, further studies with participant feedback and human factor testing are needed to ensure that the system meets the needs, values, and preferences of people who use opioids, in addition to establishing the system's safety vis-à-vis its potential to encourage moral hazard. Other harm reduction interventions such as take-home naloxone programs have been found not to increase risky behavior or lead to adverse health consequences (42)(43)(44). Previous data on harm reduction interventions show that people are willing to engage in behaviors to help keep themselves safe, such as using needle exchanges, take-home naloxone, face shields for mouth-tomouth respiratory support, and SIFs (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…The reviewed work demonstrates that patients at risk of opioid overdose presenting to the ED are willing to accept take-home naloxone, which is consistent with previous related research. 17 , 19 , 20 , 23 While the evidence regarding the effectiveness of the intervention is poor, one study reported that16% of patients who received naloxone kits went on to use it in the rescue of an opioid overdose. 23 Even with this potential for harm reduction and the acceptance among patients and providers, the practice of prescribing take-home naloxone was overall low.…”
Section: Discussionmentioning
confidence: 99%